2006
DOI: 10.1007/s10705-006-9058-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake and export from an Australian cotton field

Abstract: Soil fertility may decline as a result of nutrient export from high-yielding cotton crops and this may limit the productivity of future crops unless these nutrients are replaced. Uptake of nutrients by cotton (Gossypium hirsutum L.) and nutrient export from the field in seed were measured within two cropping systems experiments from 1999 to 2005 in a flood-irrigated cotton field. Lint yields of the seven crops assessed ranged from 975 to 2725 kg lint/ha. Nutrient uptake was measured at mid to late boll-fill an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 17 publications
5
43
0
8
Order By: Relevance
“…The values for total N uptake of sole cotton, ranging from 110 to 127 kg ha −1 in 2002, 2003 and 2004, were within the range (67-403 kg ha −1 ) reported by Rochester (2007), but lower than found by Ishaq et al (2001) and Sainju et al (2006). Total N uptake did not differ from the monoculture in any intercropping system in 2002; however, in 2003 similar N uptake as in monoculture was only found in intercropping systems 3:2 and 4:2 and a lower uptake in the 3:1 and 6:2 systems.…”
Section: Discussionsupporting
confidence: 82%
“…The values for total N uptake of sole cotton, ranging from 110 to 127 kg ha −1 in 2002, 2003 and 2004, were within the range (67-403 kg ha −1 ) reported by Rochester (2007), but lower than found by Ishaq et al (2001) and Sainju et al (2006). Total N uptake did not differ from the monoculture in any intercropping system in 2002; however, in 2003 similar N uptake as in monoculture was only found in intercropping systems 3:2 and 4:2 and a lower uptake in the 3:1 and 6:2 systems.…”
Section: Discussionsupporting
confidence: 82%
“…In cotton, crop biomass has been reported to correlate well with lint yield [36]. Studies conducted to assess yield prediction from remote sensing have generally showed that lint yield correlates better at early-mid stages of the crop with NDVI than with chlorophyll-sensitive indices [15][16][17].…”
Section: Lint Yield Predictionmentioning
confidence: 99%
“…14-24 kg -1 seed cotton in Rajasthan to Tamilnadu during 2007-09 which was basis for MSP [11]. 5.6.1 Fertilizer consumption steeply increased from 2005 onwards (Fig.…”
Section: Cost Of Production In India Variesmentioning
confidence: 96%
“…8)[41]- [43]. Fertilizer input cost was beyond doubled in 2011 after introduction of nutrient based subsidy system [6], [11]. (Fig.…”
Section: Cost Of Production In India Variesmentioning
confidence: 99%